Genetic tools for studying cochlear inhibition - Slika, Eleftheria; Fuchs, Paul Albert (Frontiers in Cellular Neuroscience, 2024)
Efferent feedback to the mammalian cochlea includes cholinergic medial olivocochlear neurons (MOCs) that release ACh to hyperpolarize and shunt the voltage change that drives electromotility of outer hair cells (OHCs). Via brainstem connectivity, MOCs are activated by sound in a frequency- and intensity-dependent manner, thereby reducing the amplification of cochlear vibration provided by OHC electromotility. Among other roles, this efferent feedback protects the cochlea from acoustic trauma. Lesion studies, as well as a variety of genetic mouse models, support the hypothesis of efferent protection from acoustic trauma. Genetic knockout and gain-of-function knockin of the unique α9α10-containing nicotinic acetylcholine receptor (nAChR) in hair cells show that acoustic protection correlates with the efficacy of cholinergic inhibition of OHCs. This protective effect was replicated by viral transduction of the gain-of-function α9L9’T nAChR into α9-knockout mice. Continued progress with “efferent gene therapy” will require a reliable method for visualizing nAChR expression in cochlear hair cells. To that end, mice expressing HA-tagged α9 or α10 nAChRs were generated using CRISPR technology. This progress will facilitate continued study of the hair cell nAChR as a therapeutic target to prevent hearing loss and potentially to ameliorate associated pathologies such as hyperacusis.